Pengaruh Work Life Balance dan Pengembangan Karir terhadap Kinerja Karyawan pada Biskop XXI Grand Kota Bintang - Putra Danaya, Bayu; Kurniawan, Dodi; Sahlan, Fahmi; Wibowo Noor Fikri, Adi; Indra Wahyu Putra, Christophorus (Fibonacci: Jurnal Ilmu Ekonomi, Manajemen dan Keuangan, 2025)
The purpose of this study was to determine the effect of work-life balance and career development on employee performance at Bioskop XXI Grand Kota Bintang. This study used a quantitative method with a sampling technique, namely saturated sampling. The population in this study were 72 employees at Bioskop XXI Grand Kota Bintang. The number of samples in this study was 72 employee respondents at Bioskop XXI Grand Kota Bintang. The measurement scale used was a Likert scale (1-5). The tests carried out in this study were the outer model test, inner model test, and hypothesis test using the SEM-PLS technique using SmartPLS statistical software. The results of the study conducted at XXI Grand Kota Bintang Cinema are as follows: 1) Work Life Balance has a positive and significant effect on Employee Performance; and 2) Career Development has a positive and significant effect on Employee Performance.